Reinterpretation of Non-Muslim Leadership Interpretation in Maqashidi Exegesis - Lalu Riastata Al Mujaddi; Zainul Ashri; Roni Irawan; Subhan Subhan (Spiritus: Religious Studies and Education Journal, 2024)
This study examines the contentious issue of Muslim-non-Muslim relations, particularly in the context of leadership and friendship. The controversy surrounding this topic stems from apparent contradictions within Quranic verses, which prohibit Muslims from forming close relationships with non-Muslims, while concurrently promoting justice and kindness towards them. Furthermore, divergent interpretations of the term awliya' among Islamic scholars have exacerbated the problem. By employing a maqashidi exegetical framework, this research aims to re-interpret the seemingly contradictory Quranic verses and reconcile the polarized approaches to exegesis. The findings of this study reveal that a chronological analysis of the relevant verses indicates a shift in address from hypocrites and Jews to those who betray God and His Messenger, irrespective of their religious affiliation. From a maqashidi perspective, these verses do not prohibit Muslims from engaging in positive relationships with non-Muslims, but rather serve as a motivation to foster a just and non-treacherous human community. Muslims are, however, prohibited from forming close relationships with treacherous individuals.